Veículo aéreo não tripulado (VANT) aplicado em mapeamentos de loteamentos do município de Pau dos Ferros - RN - Lima Neto, Mozar Leite de Araújo (Universidade Federal Rural do Semi-Árido, 2019)
Urban development is linked to many factors, such as the capitalist mode of production, the relations between individuals and the forms of occupation of space. The present research has as main objective to perform aero-surveys with the use of Unmanned Aerial Vehicle (VANT) in subdivisions of the municipality of Pau dos Ferros-RN to identify its characteristics and environmental and urban planning legality. As methodological procedures, an exploratory analysis was performed, being a qualitative and quantitative part in 23 (twenty-three) allotments in the mentioned municipality. The results revealed that all the subdivisions have deficiencies regarding the basic infrastructure, besides the Municipal Secretariat of Infrastructure, no document or data of what is being carried out in these allotments. It was also observed that some subdivisions analyzed are not properly regular with the Taxation Office and in the Real Estate Registry Office in the municipality of Pau dos Ferros / RN, and most of the landowners are in default with the municipality. Another important point to note is that only 3 (three) lots have an Environmental License and the Municipal Environment Department is not aware of those who are in the licensing process. It was evidenced the importance that drone use brings to perform tasks such as these, which, although involving large areas, aerolevantamento lasts a few minutes and, when combined with other software, provides high quality jobs.
Monografia
Keywords: Tecnologia; parcelamento do solo urbano; infraestrutura; meio ambiente; technology; installment of urban land; infrastructure; environment; ENGENHARIAS::ENGENHARIA CIVIL